EFEKTIVITAS UU PERS DALAM MENJAMIN KEBEBASAN PERS DALAM MENANGGANI TINDAK PIDANA PERS: STUDI KASUS BAND SUKATANI DALAM LAGU “BAYAR, BAYAR, BAYAR” YANG BERUJUNG DIBREDEL POLISI - Panjaitan, Vanny (Fakultas Hukum Universitas Gunung Rinjani, 2025)
Abstract Press freedom is a constitutional guarantee as stipulated in Law Number 40 of 1999 on the Press. Nonetheless, this freedom is not without boundaries and may be restricted by law. This research explores the adequacy of legal safeguards for press freedom and freedom of expression through a normative juridical approach, using the case of Band Sukatani as a focal point. The case reveals a disconnect between existing legal provisions and their real-world application, exemplified by the censorship of the song